POLA PERILAKU KEBERAGAMAAN SISWA DI SEKOLAH UMUM (Studi Pada SMAN1 dan SMAN 2 Kota Samarinda) - Arifuddin Ismail (Balai Penelitian dan Pengembangan Agama Makassar, 2008)
This research aims to describe religions comprehension, attitude, andbehavior of high school student. This was conducted in SMAN 1 andSMAN 2 Samarinda, East Kalimantan. Data was collected using questionerto among one hundred students of both high schools, and analyzedusing quantitative method.The result of research showed that religious comprehension, attitude,and behavior of high school student at good level. It means that moststudents of high school have good comprehension, good attitude, andgood behavior. But, this research also showed that few students havebad comprehension, and bad behavior.